Distributed Video Tracking - Phon, Thamiet Saukeaw (2018)
This project is conducted to test out the distributed video tracking system in surveillance monitoring. The main objective of this project is to develop an algorithm to track a target based on the target parameters across multiple camera in an integrated embedded camera platform. For monitoring and security purpose, there are a lot of camera throughout the world. The ratio of an operator and thousands of cameras are deemed ineffective and there are possible of recklessness. In this project, we will come out with an effective way surveillance and monitoring through algorithm for video tracking. There are three main phases for the algorithm for video tracking: object recognition, data transmission, object tracking. The focus of the project will be more on object recognition based on colour and shape features. The first Raspberry Pi will send the data feature of colour and shape to the second or next Raspberry Pi and it will track based on the data received. As for research methodology, proper planning is very important to make sure the project is of good quality and to finish on time. As a conclusion, we hope this project will be useful in surveillance monitoring by implementing the distributed video tracking across the country or the world.